Damage and crop loss relationships of Helopeltis theivora, Hemiptera, Miridae and cocoa in Malaysia - Muhamad, R.; Way, M.J. (Elsevier, 1995)
Miridae cause serious crop loss of cocoa worldwide yet the relationship between feeding damage and survival of cherelles and pods is inadequately understood, particularly in terms of timing of damage and also of other sequential mortalities that occur throughout development from the flower bud to the ripe pod stage. Five post-flowering developmental stages were used as a basis for assessing crop loss in relation to Helopeltis theivora feeding damage in Peninsular Malaysia. These include 'cherelle initiates', which invariably abscind after only one H. theivora feeding lesion. Subsequently, cherelles may die and wilt but do not abscind. Cherelle wilt was strongly linked to time and number of feeding lesions, such that older cherelles tolerated notably more damage than was needed to kill young cherelles. Pods from surviving severely damaged cherelles were smaller and contained smaller seeds although the number of seeds per pod was unaffected. However, yield was most affected by H. theivora-associated death of cherelles. Growing pods were killed by artificially created intense short-term attack by H. theivora but this is unlikely in nature where there may be much greater extended damage throughout development of a pod that survives. The yield of full-sized pods was unaffected by artificially imposed very severe attack. An experiment on possible compensation for cherelles killed by H. theivora indicated that the number and weight of seeds per pod is already determined at the early cherelle stage. A life table of survivorship from the flower bud to the ripe pod stage showed very large mortalities of buds and flowers but, in terms of survival to ripe pods, the crucial proportional mortality is during the mirid-susceptible cherelle stage.